Sarah Gray Cary from Boston to Grenada : Shifting Fortunes of an American Family, 1764-1826 - Imbarrato, Susan Clair (Book collections on Project MUSE., 2018)
"Susan Imbarrato tells the story of the Cary family of Chelsea, Massachusetts, who prospered as plantation owners and managers for nearly two decades in Grenada before their fortunes were substantially reversed following the slave revolts of 1795-1796 that upended the sugar trade and marked a significant turning point in the family's financial and social well-being. Working closely with archival materials that include letters, diaries, newspapers, a plantation manual, and business memoranda, the author places the Cary family story within the larger context of the transition from colonial America to the new republic and against the backdrop of the transatlantic sugar trade, the slave revolts, and the early abolitionist movement. With Sarah Gray Cary's quick intelligence and astute assessments as their guide, the Cary family adapts to their shifting fortunes in remarkable ways. This study offers a new perspective on this time period using the extensive mother-son correspondence as they address family matters, share opinions on political and social events, discuss literature and philosophy, and speculate on business and career possibilities. Throughout, Sarah provides a steadying influence that both sustains and encourages, all the while successfully managing households in both Grenada and Chelsea that will eventually include thirteen children. The methodology of this study combines New Historicism with close readings. A must-read for historians, literary scholars, students, and the general public interested in American history and literature, women's history, the transatlantic sugar trade, slavery, abolition, letter writing, family correspondence, the Revolutionary Era, and the new republic"--